‘That clauses’ as Subjects: Strategies for Avoidance - Talat Masood (Social Science Review Archives, 2025)
This paper deals with the usage of ‘that clauses’ as the subjects of sentences. It explores how constructions that have ‘that clauses’ as subjects behave in different languages. This study tries to determine how sentences that have ‘that clauses’ as subjects try to avoid clausal subjects by resorting to different strategies. For this purpose, a sample of three languages is chosen. The study establishes that sentences that have ‘that clauses’ as subjects behave almost the same in terms of different features; however, when it comes to different avoiding strategies then languages differ. For this preference for alternate strategies among different languages different factors have been proposed to play their role. These factors could be extended to other languages to establish a cross-linguistic hierarchy for alternate strategies to avoid ‘that clauses’ as subjects.